Histoscanning and shear wave ultrasound elastography for prostate cancer diagnosis - A. V. Amosov (Onkourologiâ, 2016)
Introduction. The shear wave ultrasound elastography is a recently developed ultrasound-based method in the clinical practice, which allows the qualitative visual and quantitative measurements of tissue stiffness. In the 2010 this technology of the shear wave was called Shear Wave Elastograhpy. Due to the front of the shear waves the qualitative and quantitative assessment of the tissue stiffness is possible.Objective is to examine the efficacy of the shear wave ultrasound elastography in the evaluation of the prevalence of the oncological disease in patients with the prostate cancer and to compare the obtained results with the routine method X-ray diagnostics.Materials and methods. From the april 2015 in the I.M. Sechenov First Moscow State Medical University Urology Clinic there were conducted 314 shear wave ultrasound elastography examinations of the prostate. The ultrasound system Aixplorer® by SuperSonic Imagine was used. This system provides information provided by B-mode and shear wave ultrasound elastography mode. The transrectal echograms were made in 6 dimensions, so called Q-boxes (3 demensions in the every lobe on the segments from the base to the apex, according to the biopsy zone). The unit of measurement was the mean value in the kilopaskals (kPa). All the patients were randomized into 3 groups. There were 146 men with the possible prostate cancer in the first group (prospective study), 120 men with the certain diagnosis of the prostate cancer in the second group (retrospective study) and 48 healthy men in the third group (control study). In all the patients of the first and the second groups the routine complete examination, including the prostate specific antigen (PSA) level examination, digital rectal examination (DRE), doppler transrectal ultrasonography (TRUS), histoscanning and ultrasound shear wave elastography (SWE), was conducted. In the 229 patients of the first and the second groups the prostatectomy with the morphological verification of postoperative material was made. In the 63 patients of the first and the second groups the contrast-enhanced magnetic resonance imaging (MRI) of the pelvic organs was made. In the health men’s group, besides the ultrasound shear wave elastography, only the routine diagnosis methods of the prostate cancer (PSA level, TRUS and DRE) were used.Results. According to the results of our study, the threshold values for the normal prostate tissue stiffness due to the ultrasound shear wave elastography were from 0 to 23 kPa, for the hyperplastic prostate – from 23.4 to 50 kPa, for the prostate cancer – from 50.5 kPa. The data analysis of the 212 patients with the verified prostate cancer showed the increase of the mean degree of tissue stiffness due to the clinical stage and tumor differentiation (Gleason scale total score). All the patients were divided into the subgroups with the certain correlation values. In patients with the Gleason scale total score < 7, the mean degree of tissue stiffness was 72 kPa (n = 63). In 57 patients with the Gleason scale total score 7, the mean degree of tissue stiffness was 69 kPa. In 48 patients with the Gleason scale total score from 8 to 10, the tissue stiffness was averagely 119 kPa. The locally advanced stage Т3–4 was determined in 44 examined patients. The tissue stiffness value correlated with the tumor differentiation rate: the index variations were from 120 to 295 kPa. On the results of this method analysis, its resistance was 90,8 % and specificity was 94,6 %. According to the comparative assessment with the other examination technics, the informative value of the ultrasound shear wave elastography is far above the DRE, the doppler TRUS and the histoscanning, but is lower than the contrast-enhanced magnetic resonance imaging.Conclusion. In view of the above, the ultrasound shear wave elastography is a very informative method of the prostate cancer detection and it has a high rate of the agreement of the results with the contrast-enhanced magnetic resonance imaging and is more specific than the histoscanning.